The Politics of Responsibility - Lavin, Chad. ([S.l.]: University of Illinois Press, 2007)
Politics cannot function without responsibility, but there have been serious disagreements about how responsibility is to be understood and huge controversies about how it is to be distributed, rewarded, legislated, and enforced. The liberal notions of personal responsibility that have dominated political thinking in the West for more than a century are rooted in the familiar territory of individual will and causal blame, but these theories have been assailed as no longer adequate to explain or address the political demands of a global social structure. Informed by Marx, Foucault, and Butler, Chad Lavin argues for a "postliberal" theory of responsibility, formulating responsibility as a process that is anchored in a persistent ability to respond, not reproach. Lavin works this formulation through discussions of contemporary political issues such as globalization, police brutality, and abortion. Rather than assigning individual blame, postliberal responsibility challenges the supposed autonomy of individual subjects by taking structural arguments into account. Lavin concludes that a liberal concept of responsibility gives rise to a moralistic and oppressive approach to social problems, while a postliberal approach highlights a shared responsibility for developing collective solutions to systemic problems. Postliberal responsibility not only suggests more generous and democratic responses to social ills, it also allows us to theorize a greater range of issues that demand political response.
Electronic book.
Professional and scholarly.
Online resource; title from digital title page (cloudLibrary, viewed November 28, 2024).
eBooks on EBSCOhost
Keywords: Responsibility; Political science -- Philosophy; Responsabilité.; Political; PHILOSOPHY; Social; History & Theory; Electronic books